Acute Respiratory Distress Syndrome immediately following the removal of an aspirated foreign body. (2020) - Simpson, Ryne; Myer IV, Charles; Siracusa, Christopher
Abstract: Acute Respiratory Distress Syndrome (ARDS) is a form of diffuse lung injury with many potential etiologies, pneumonia being the most common cause developing outside of the hospital. Foreign body (FB) aspiration is a risk factor for pneumonia, and therefore, ARDS. Although these associations exist, the development of ARDS immediately following the removal of an aspirated FB appears quite rare. We present the case of an 11 year old male who was found to have a right-sided, post-obstructive pneumonia secondary to an aspirated FB obstructing the bronchus intermedius. Relief of the obstruction allowed for rapid, endobronchial spread of infection and within 6 hours of FB removal, our patient developed severe ARDS requiring initiation of extracorporeal membrane oxygenation (ECMO). Streptococcus constellatus was isolated from lower respiratory cultures obtained during initial bronchoscopy.